Analisis Pengaruh Kecerdasan Intelektual, Kecerdasan Spiritual dan Kecerdasan Emosional Terhadap Kinerja Karyawan - M Haidar Ali; Hadi Sunaryo; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The goal of this study is to determine and examine how intellectual, spiritual, and emotional intelligence affect CV workers' performance. The Pasuruan Sido Rame Makmur. Research of this kind is quantitative. This study is a census-based study. In this study, there are two types of data sources: primary data and secondary data. A questionnaire and a Likert scale are used in the research data collection process. The findings of this study suggest that employee performance is influenced by intellectual, spiritual, and emotional intelligence. Spiritual intelligence, emotional intelligence, and spiritual intelligence all have a substantial impact on an employee's performance. Intellectual intelligence has little to no impact. Keywords: Intellectual Intelligence, Spiritual Intelligence, Emotional Intelligence and Employee Performance.